Positive orientation and the perception of feedback in foreign language learners - Kiński, Czesław; Kiński, Bartosz (Neofilolog, 2024)
The primary aim of the present study is to examine the relationship between foreign language learners’ positive orientation and their perception of teacher and peer feedback. It also investigates gender differences and the relationship between the frequency of receiving feedback and the perception of its different dimensions. 429 foreign language university students were asked to complete an online questionnaire. Subsequently, statistical analysis of the data was carried out in order to obtain results, which indicated that positive orientation positively correlated with the feeling of comfort while receiving feedback, regardless of source or setting. Regarding the differences between genders, it was found that men felt more comfortable than women receiving feedback highlighting their mistakes and feedback given in public; conversely, women preferred feedback focused on positive aspects and feedback given in private. Finally, it was observed that students who receive feedback often feel more comfortable with the potentially stressful dimensions, such as a public setting and focus on mistakes. The most important pedagogical implication is that teachers should provide feedback regularly and employ strategies to boost their students’ positive orientation levels, which may in turn lead to their increased satisfaction from receiving feedback.